THE FIGHT AGAINST FRAUD IN THE EUROPEAN UNION - Mihaela Iuliana DUMITRU; Diana Elena BRINZA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2021)
The aim of the work is to highlight the efforts and the activity carried out at the level of the European Union in the direction of the fight against fraud, both at a general level and especially in terms of ensuring a favorable climate for the functioning and development of economic mechanisms. The totality of these actions is more and more extensive, given that the access to the Community financial support is currently facilitated, as a result of the particular conditions generated by the pandemic. Community financial assistance is seen as a necessary 'breath of oxygen', but not sufficient to support economic and financial activities.